2012
DOI: 10.1007/s00432-012-1349-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation study of a prognostic classification in patients with metastatic colorectal cancer who received irinotecan-based second-line chemotherapy

Abstract: The previous prognostic classification of patients with MCRC who received irinotecan-based second-line chemotherapy was validated in another independent cohort. Validation in prospective studies is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure describes the search results. The scientific literature review and web‐based search identified 53 tools predicting survival in colon or rectal cancer, reported across 63 articles . Two articles reported on the development of two tools each .…”
Section: Resultsmentioning
confidence: 99%
“…Two articles reported on the development of two tools each . Eighteen articles contained external validations only . One article updated two tools with additional prognostic information .…”
Section: Resultsmentioning
confidence: 99%
“…The serum levels of LDH and carcinoembryonic antigen, which have been previously reported to be associated with tumor burden and poor prognosis [29] , were significantly higher in cohort C. Regarding the third-line treatment regimen, many patients in cohorts A and B were treated with anti-EGFR antibody as the third-line or subsequent treatment. Regarding the chemotherapy platform as first-line treatment in our study, about one third of patients in cohort C were administered FOLFIRI, which demonstrated the survival advantage adding anti-EGFR antibody to FOL-FIRI in the two previous phase III trials [30] .…”
Section: Discussionmentioning
confidence: 97%
“…Before this study, there was some indication that TTP <6 months after beginning first-line treatment may be a negative prognostic factor among patients undergoing irinotecan-based second-line therapy [11]. The RAISE study stratified patients by first-line TTP <6 versus ≥6 months and then examined the data following the study to determine whether TTP on first-line therapy was prognostic for OS.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age has been associated with more pronounced or frequent safety concerns; as a result, the risk–benefit balance of cancer treatments in the elderly population has been under scrutiny [10]. In some cases, patients with more and less aggressive disease, as assessed by time to progression (TTP) on first-line therapy, could have differential responsiveness to second-line therapy [11]. …”
Section: Introductionmentioning
confidence: 99%